Supplier integration, operational capability and firm performance: an investigation in an emerging economy environment. Issue 13 (2nd October 2020) - Amoako-Gyampah, Kwasi; Boakye, Kwabena G.; Famiyeh, Samuel; Adaku, Ebenezer
Abstract: The literature on supplier integration's (SI) impact on firm performance is intertwined with mixed findings in terms of definitional differences, study context, specific integration components, and the types of relationships examined. This study contributes to the supplier integration and firm performance (SI-FP) literature by investigating how and when supplier integration influences firm performance. Drawing on the relational view, the resource-based view, and the Dynamics Capability theories, we suggest that improvements in firm performance from the supplier integration perspective are dependent on gains in operational capabilities. We test this dependency with survey data from firms in Ghana, a developing economy. The results show positive significant relationships between supplier integration and competitive operational capabilities and between supplier integration and firm performance. Our results highlight the importance for managers in developing economies and elsewhere to improve their firms' operational capabilities and competitiveness by investing in supplier integration. We also discuss implications of these findings for research.